(untitled) (Scientia Agricola, 2019)
Plants of Coffea arabica Icatu IAC 925 germplasm show resistance to Meloidogyne paranaensis under field conditions, but with variable rates of segregation. One mother plant, IAC 3, of Icatu IAC 925 was evaluated under controlled conditions through the reaction of its clones, obtained by somatic embryogenesis. Reproduction of nematodes in clones were compared with an open-pollinated progeny from the same mother plant, C. arabica cultivar Mundo Novo IAC 515-20, susceptible to nematodes, and Clone IAC 1, also susceptible and obtained by somatic embryogenesis. Open-pollinated progeny showed segregation to resistance and was classified as susceptible according to the reproduction factor. The average number of nematodes (eggs and J2) per gram of roots in clones was eight fold lower than that of open-pollinated progeny, and 51 fold lower than Mundo Novo IAC 515-20. Based on Seinhorst model, IAC 3 clone showed a tolerance limit of 7.7 nematodes per cm3 of soil, while in Mundo Novo the tolerance limit was 3.9 nematodes per cm3 of soil. These results revealed that clonal Arabica coffee nematoderesistant trees represent an alternative to the time consuming and expensive process inherent to conventional breeding strategies.